Sources of occupational pressures for civil protection agents A field study at the Central Unit of Civil Protection - Skikda - .bouatit, djelal; mirouh, abdelouahab (Journal of Social Sciences and Humanities, 2023)
The purpose of this study is to identify the sources of occupational stress among civil protection agents. Specifically, this study addresses three dimensions of occupational stress: role ambiguity, workload, and working conditions. A form that measures these dimensions was used to identify indicators of occupational stress. The study methodology used was a descriptive approach, and a simple random sample was selected from the total study population of civil protection agents. Methods for processing quantitative and descriptive data were also defined. Results of the study indicate the presence of occupational stressors among civil protection agents, although the rates of their presence or spread differed. Role ambiguity was found to manifest in contradictory tasks, responsibility for separate tasks from those to be performed, lack of clarity in work procedures and rules, and ambiguity in tasks performed. Working conditions were found to manifest in a polluted work environment, lack of work equipment, noise, and an unhealthy environment. As civil protection is an arduous profession, it is important to understand and address the sources of pressure to support the well-being of these professionals.